HUMAN RESOURCES TRAINING IN BIOTECHNOLOGY: MICROALGAE FOR BIOFUEL AND WASTEWATER TREATMENT. - Moraes, Iracema de Oliveira; Arruda, Regina de Oliveira Moraes; Moraes, Rodrigo de Oliveira; Moraes, Maria Josiane Conti (Revista Geociências - UNG-Ser - ISSN 1981-741X (1981-7428), 2019)
The most promising and innovative alternative to biodiesel production is presented by the algae (micro and macroalgae), which have been classified by scientists as a source of third generation biofuels. The large-scale production of biodiesel from microalgae and macroalgae bioethanol production will happen much faster than you think. It is believed that its full commercialization is possible within a few years, and with a competitive price compared to diesel produced from petroleum, the same occurring for bioethanol. The use of seaweed as a feedstock for the production of biofuels has been seen as a less environmentally impactful as the biomass produced on the continent and its potential is very high. Several groups in Latin America (Brazil, of course) are studying micro and macroalgae not only for biofuels production (biodiesel, bioethanol, biohydrogen) but also to do wastewater treatment. This paper will discuss the presentations done in four annual courses (2010, 2011, 2012, 2013) promoted by the Biotechnology Brazilian Argentine Center, BBAC, and offered to fellowships (sixteen per year), from Brazil, Argentina, Colombia, Paraguay and Uruguay. Arthrospira (Spirulina) platensis was chosen as a cyanobacteria model in the courses, due to its feasibility of cultivation, many publications about the subject and the existence of strains isolated in Brazil.